A Case of Covid-19 Patient Presenting with Gastrointestinal-Specific Symptoms in Indonesia - Daniel Martin Simadibrata; Cleopas Martin Rumende; Rahmad Mulyadi; Marcellus Simadibrata (The Indonesian Society for Digestive Endoscopy, 2020)
Coronavirus disease 2019 (COVID-19) is an emerging infectious disease officially declared as a pandemic on 11 March 2020 by the World Health Organization (WHO). Indonesia’s COVID-19 case fatality rate remain consistently high, approximately twice the global case fatality rate available. Patients typically present with fever, dry cough and dyspnea. However, there were reports of atypical COVID-19 symptoms such as myalgia, fatigue, diarrhea, nausea, and vomiting. These atypical presentations were suggested to indicate a more severe COVID-19. Here, we present a case of COVID-19 patient presenting with gastrointestinal-specific symptoms in Indonesia.